EXPERT'S CONCLUSIONS IN CRIMINAL INVESTIGATIONS OF CONSTRUCTION FRAUD - Andrei Yu. Butyrin; Igor' A. Danilkin (Теория и практика судебной экспертизы, 2018)
The paper analyzes various forms of conclusions presented in forensic construction audit reports. Representative examples from forensic casework are included to demonstrate the circumstances warranting the use of categorical assertions, categorical exclusions, conditional, alternative, or probable conclusions in a forensic construction audit report. The issues of expert report evaluation are examined in terms of assessing the probative value of expert opinions presented in different logical forms in a forensic construction audit report. Arguments are offered in support of using construction audit reports with probabilistic conclusions as a source of evidence in criminal investigations.